DETERMINAN KINERJA KEUANGAN PEMERINTAH DAERAH - Amin Insani; Rahayu, Sri; Misni Erwati (Faculty of Economics and Business University of Mataram, 2023)
Local government financial performance is an indicator used to monitor, measure, evaluate, and achieve the implementation of effective and efficient regional financial management. The research aims to determine the effect of local original income, balancing funds, capital expenditure, economic growth, and audit opinions on the financial performance of district/city governments in Jambi Province for the 2019-2021 period. A total of 33 samples in 11 districts/cities were obtained using a non-probability sampling technique. Secondary data was obtained from the official websites of DJPK, BPS, and BPK Jambi province. The results showed that the variable of local original income had a positive influence on the financial performance of local governments and the variable of equalization funds had a negative influence on the financial performance of local governments, but for variables of capital expenditure, economic growth, and audit opinions did not affect the financial performance of local governments. The results of this study make an important contribution in efforts to improve government performance and services to the community.